Peranan Administrasi Pendidikan - Khumairani, Annisa; Hasanah Usnur, Uswatun (STAI Tebing Tinggi Deli, 2024)
This research discusses the role of educational administration, in this case, the learning device as an effort to increase Islamic education teacher professionalism at MTS MUHAMMADIYAH Sei Rampah, Serdang Bedagai Regency. The aims are to analyze: 1) the state of educational administration made by the teacher; 2) the form of teacher professionalism; and 3) the contribution of educational administration in increasing teacher professionalism. The type of this research is qualitative with descriptive method. Informants in this research were teachers of Al-Qur’an-Hadis, teachers of Akidah Akhlak, teachers of Fikih, and teachers of Islamic Culture History (SKI) at MTS Muhammadiyah SeiRampah, Serdang Bedagai Regency. The results showed that the state of teacher education administration at MTS Muhammadiyah, Serdang Bedagai Regency was complete and was well applied in the learning process in the classroom. The form of teacher professionalism is carrying out duties, roles, and responsibilities as teachers well. The contributions of educational administration in developing teacher professionalism at MTS Muhammadiyah, Serdang Bedagai Regency are five, namely: (1) time management, (2) class management, (3) stimulating to innovate, (4) stimulating to develop technical skills, (5) and the concept of transformation of students.